"Information specialist skills in dealing with open source software at the Library of the humanities and social sciences faculty, Setif 2 University - Algeria " - ikhlef, fatimazohra; karim, mourad (Journal of Social Sciences and Humanities, 2025)
Open-source software is characterized by several features that have made it the focus of attention for libraries and information centers. pmb software is considered one of the most important systems that university libraries have adopted due to the extensive capabilities it offers to facilitate the performance of functions and provide services in a more efficient manner. In this context, the aim of this study was to assess the extent to which information specialists at the Library of the Faculty of Humanities and Social Sciences at Setif 2 University possess the necessary skills to deal with the open-source software pmb. The study’s findings revealed a lack of sufficient knowledge about the software, as well as a deficiency in the technical and technological skills required to ensure its effective use.